The Effectiveness of Using Quizizz to Improve the Students’ Vocabulary - Nabila, Hesti; Muliati, A.; Talib, Ahmad (Journal of Excellence in English Language Education, 2023)
This study aims to determine the effectiveness of using Quizizz application to improve the students’ vocabulary. The method used was quantitative with a pre-experimental research design with a sample of 30 students of class VIIC. In obtaining data, the researcher used pretest and posttest as instruments. The results of the data analysis showed that by using the Quizizz application, students’ vocabulary mastery increased. This is demonstrated by the fact that the t-test value is less than P (0.001 0.05), meaning that H0 in this research is rejected and H1 is accepted. Thus, it was determined that using the Quizizz app to improve vocabulary mastery was effective for class VII. C students at SMP Negeri 1 Campalagian.